2004
DOI: 10.1007/s00280-003-0750-5
|View full text |Cite
|
Sign up to set email alerts
|

Interaction pharmacokinetics of pegylated liposomal doxorubicin (Caelyx) on coadministration with paclitaxel or docetaxel

Abstract: This study showed the presence of a pharmacokinetic interaction that led to higher plasma concentrations of PLD when combined with paclitaxel and to a minor extent when combined with docetaxel. This pharmacokinetic information may be of value when planning combination therapies of PLD with taxanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Delays in clearance of PLD have been observed clinically when PLD was combined with taxanes (46)(47)(48). Cyclophosphamide, particularly at high doses, is known to have also immunologic effects and therefore could alter the pharmacokinetics of subsequently administered agents.…”
Section: Discussionmentioning
confidence: 99%
“…Delays in clearance of PLD have been observed clinically when PLD was combined with taxanes (46)(47)(48). Cyclophosphamide, particularly at high doses, is known to have also immunologic effects and therefore could alter the pharmacokinetics of subsequently administered agents.…”
Section: Discussionmentioning
confidence: 99%
“…DOXIL/Caelyx is now undergoing trials for treatment of other malignancies such as multiple myeloma (Hussein and Anderson 2004), breast cancer (Robert et al 2004), and recurrent high-grade glioma (Hau et al 2004). Several studies are under way to investigate the anticancer activities of PLD in combination with other therapeutics, including the taxanes (paclitaxel or docetaxel) (Briasoulis et al 2004; Vorobiof et al 2004), temozolomide (Temodal ® Schering-Plough, Kenilworth, NJ, USA) (Awada et al 2004), and vinorelbine (Katsaros et al 2005). …”
Section: Long-circulating Liposomesmentioning
confidence: 99%
“…Recent clinical studies have demonstrated higher effectiveness of multiple drug delivery compared to single drug administration, eg, in cancer therapy. 72,73 However, blended or bilayered particles loaded with multiple drugs do not allow control of individual drug release. 74 Several techniques, such as microfluidic techniques and layerby-layer self-assembly and emulsion, were suggested to enable separate regulation of multiple drug-release kinetics.…”
Section: Coaxial Electrosprayingmentioning
confidence: 99%